Skill Shortage versus Subject Choice: Case of Pakistan (The Pakistan Development Review, 2009)
Higher Education is believed to be a very important determinant of economic growth. The growth can be optimised with a suitable combination of skills in various subjects. A mismatch between required combination of skills and available combination of skills carries heavy costs for developing economies since import of skill from foreign is much more in expensive for such economies. We compare skill shortage in Pakistan with the subjects choice of students recently enrolled in institutes of higher learning. We found that there is a mismatch between skill shortage and the enrolment trend. We propose that the Government should regulate recruitment of students into various subjects in order to create greater harmony between national needs and students enrolment. JEL classification: J08, J82 Keywords: Subject Choice, Skill Shortage, National Needs